”The Truth” in Thai Criminal Justice System: Legal Perspectives on the Literature in Chomanee’s Rak Boon - อัจฉริยะประสิทธิ์, จิราภรณ์; ชูวัฒนกิจ, ไพบูลย์ (CMU Journal of Law and Social Sciences, 2018)
The “truth” in Thai criminal justice system is very important because it is what we believe that it provides fairness to the society, victims, including defendants. In this case, the investigation or court’s hearings are conducted in order to allow the truth to be appeared. In this article, it analyzes the definition and the investigation on “truth” in the novel titled Rak Boon of Chomanee by using a critical and Feminist Legal Theory to reveal the ideas, beliefs, or prejudices that lie behind the process of the truth investigation appeared in the novel. From the study, it was found in the novel presented that the truth was important to the victim and the proof of crime. The appeared truth had a complex meaning, both in terms of proving the offence and in terms of revealing life, mind, and reality behind the scenes that were not usually appeared in legal. The female characters were created to play an important role in solving the case and help revealing the truth through specific methods. The voice of the dead that was uttered to the main female character reflected the claim of fairness and the need for the truth to appear; whereas, it illustrated the lack of some points of the Thai criminal justice system and the action of taking advantages of marginalized people in Thai society.